Armenian arj ‘bear’ - Werner Winter (Sound Law and Analogy, 1997)
The acetabular labrum has long been a centerpiece in the treatment of femoroacetabular impingement syndrome and in our understanding of hip biomechanics. The labrum has a number of biomechanically distinct functions, including increasing the overall contact area of the hip joint, preventing synovial fluid egress from the central compartment during compressive loading, and increasing hip stability via negative pressure generation during destabilizing movements. Despite the delineation of these functions, our understanding of the labrum's influence on outcomes in hip preservation procedures is yet evolving. Labral preservation, via labral repair/refixation, has been consistently associated with greater improvement in patient-reported outcomes when compared with labral debridement. The influence of the hypoplastic labrum, a less severe labral deficiency, on surgical outcomes is an active area of investigation.